A New Approach to Channel Equalization Problem - Menguc, Engin Cemal; Acır, Nurettin (Ieee, 2015)
In this study, a new approach based on Lyapunov stability theory (LST) is proposed for channel equalization problem. For the first time, the convergence capability of the proposed algorithm is presented on the channel equalization problem. The proposed approach is compared with normalized least mean square (NLMS) algorithm. Simulation results show that the convergence capability of the proposed algorithm is better than NLMS algorithm. As a result, the proposed approach can effectively be used for the channel equalization problem.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Menguc, Engin Cemal/0000-0002-0619-549X
Keywords: Lyapunov stabiliy theory; channel equalization; convergence capability